A novel congestion-aware routing algorithm with prediction in mesh-based networks-on-chip - Akbar, R.; Safaei, F. (Nano communication networks, 2020)
Increasing the number of processing cores in the networks-on-chip in recent years has made congestion one of the most important challenges in this field. One of the best ways to solve this problem, which has greater effectiveness and less overhead, is the use of congestion-aware routing algorithm. In this algorithm, when a packet is generated, a route is selected from the minimum routes based on the betweenness centrality, history of the previous packets’ routes and the adaptivity degree. The packet tries to move as far as possible in the selected route, and in the event of extreme congestion, it can change its route for limited times and again selects a new route according to the same parameters. To be more in detail, this algorithm is a combination of deterministic and adaptive routings. In order to reduce the overhead, the adaptive routing algorithm uses only the neighboring data. The proposed routing algorithm has been compared with five different algorithms in terms of the average packet latency, power consumption and variance of the switch activities under real and synthetic traffics. In turn, the proposed algorithm has better performance through simulation experiments.